PENGARUH CAPITAL STRUCTURE, GROWTH OPPORTUNITIES, DAN ACCOUNTING CONSERVATISM TERHADAP EARNINGS RESPONSE COEFFICIENT - Elvara Stephanie, Widyasari (Jurnal Paradigma Akuntansi, 2020)
The aim of this research is to empirically examine the influence of the capital structure, growth opportunities, and accounting conservatism of the earnings response coefficient on manufacturing companies listed in the Indonesian Stock Exchange in the period of 2016-2018. The sample selection is done by purposive sampling method, and obtained a sample of 54 companies in this research. The result of this research shows that capital structure and growth opportunities have no significant effect on earnings response coefficient, but accounting conservatism negatively affects earnings response coefficient.